Equity as a prerequisite for stable cooperation in a public-good economy: The core revisited - Wolfgang Buchholz; Wolfgang Peters (Center for Economic Studies and ifo Institute (CESifo), 2010)
In this paper we explore the relationship between an equitable distribution of the cost shares in public-good provision on the one hand and the core property of an allocation on the other. In particular we show that it is an inhomogeneous distribution of cost shares that motivates some coalition of agents to separate and to block an initially given Pareto optimal allocation which can be interpreted as the outcome of a negotiation process when all agents form a grand coalition. Distributional equity of the individual burdens of public-good contribution is assessed by a specific sacrifice measure (the 'Moulin sacrifice') which is derived from the egalitarian-equivalent concept suggested by Moulin (1987). We also develop a simple core test by which it can be checked whether a given allocation is in the core thus being a possible outcome of a cooperative agreement in the public-good economy.
Keywords: C71; D63; H41; 330; public goods; core; equity; stability of cooperation; Öffentliches Gut; Kostenverrechnung; Finanzierung; Nichtkooperatives Spiel; Gerechtigkeit; Koalition; Core; Theorie